Thermal behavior of floating photovoltaics: A comparison of performance at varying heights and benchmarking against land-based photovoltaics - Ramanan, C.J.; Lim, King Hann; Kurnia, Jundika (2025)
Floating photovoltaics (FPV) offer benefits in land conservation, evaporation prevention and mitigation of PV panel thermal degradation. Previous studies suggested that enhanced cooling in FPV contributes to the improved efficiency of the PV panel compared to land-based PV (LPV) systems. However, most reported studies have constraints such as ex-situ measurements, manual data collection, data averaging, numerical analysis limitations, and limited comparison between FPV and LPV designs. These limitations hinder the accurate prediction of FPV's superior performance due to cooling mechanisms. Hence, this study investigates the performance evaluation of LPV and FPV systems in terms of 250 mm height FPV, 800 mm height FPV and 800 mm height LPV for a total measurement duration of six days. This investigation takes into account the effect of dynamic environmental parameters, including solar radiation, ambient and water temperature, humidity, wind speed and direction, and rainfall. Results reveal that the temperature of the FPV at 250 mm height reduces by more than 2 ∘C compared to the LPV at 800 mm height. It should be noted that this improvement was recorded during off-time when solar radiation is not optimal for energy generation. Meanwhile, the 800 mm height FPV demonstrates cooling at a range of 2 ∘C to 0 ∘C compared to 800 mm height LPV for 57 % of the experiment duration in time and makes it the best cooling performer. Furthermore, humidity, rainfall, fluctuating solar radiation, high wind speed and higher differences in water and ambient temperature were found to significantly contribute to FPV cooling. The resulting findings can be used to improve the accuracy of FPV performance prediction and thus contribute to the advancements of green energy technology.